How Far Can the European Parliament Correct the European Union’s Democratic Deficit? - Nicoleta Laşan (Romanian Journal of European Affairs, 2008)
Whatever the definition for democracy and democratic deficit is, the European Union is expected to develop some of the democratic features that member states present in order to compensate for the loss of legitimacy at the national level. The European Parliament, as the single elected institution of the European Union, is not only expected to comply with the basic requirements of democracy, but also to be a tool for enhancing democracy in the whole European political system. Starting the discussion by presenting the most important views expressed in the literature regarding the European Union’s democratic deficit, the paper aims to present the main strengths and weaknesses of the European Parliament in correcting the democratic deficit. It will be demonstrated that although the EP can correct the democratic deficit at the European level through its elections, the functions it performs and through its party system, it also has many limits in fulfilling this task. It can be stated that the same mechanisms which allow the EP to be a promoter of democracy inside the EU, also limit its capacity in this area and make the EP seem rather as part of the problem than a solution to it.